MAPPING CANVAS BUSINESS MODELS FOR MARKETING LOUD WISE LEATHER PRODUCTS - Azmy, Ahmad; Saputra, Adrian; Sulistianto, Hario (Jurnal Manajemen Bisnis, 2019)
This study analyzes the canvas business model application for the needs of Loud Wise's marketing strategy. The research problem found that Loud Wise must maintain the existence of products with intense business competition. The canvas business model element, combined with the marketing mix mapping, was able to map the problem and recommended marketing strategies according to product needs. The recommendations given are increasing product promotion and giving new prices to consumers. The recommendation process through marketing analysis was using the SWOT Analysis approach. Companies must prioritize handmade-based production and increase product promotion to consumers. The use of social media must be used massively so that the increase in market growth is in line with the company's business targets.